2021
DOI: 10.3390/cells10020252
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Pro-Fibrotic Effect of MIF in Non-Alcoholic Steatohepatitis Is Linked to a Shift in NKT Cell Populations

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic inflammatory cytokine with anti-fibrotic properties in toxic liver injury models and anti-steatotic functions in non-alcoholic fatty liver disease (NAFLD) attributed to the CD74/AMPK signaling pathway. As NAFLD progression is associated with fibrosis, we studied MIF function during NAFLD-associated liver fibrogenesis in mice and men by molecular, histological and immunological methods in vitro and in vivo. After NASH diet feeding, hepatic Mif expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…MIF is expressed in multiple types of both parenchymal and nonparenchymal cells present in the chronically diseased liver: For instance, MIF is secreted by adipocytes and fibroblasts as well as several immune cells, endothelial cells and Kupffer cells upon inflammatory stimuli. Interestingly, as shown by our previous study, hepatocytes represent the main source of MIF within the liver during the progression of non-alcoholic steatohepatitis (NASH) (Heinrichs et al, 2021). In the liver, CD74 is expressed on hepatocytes as well as hepatic stellate cells (HSC) (Maubach et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…MIF is expressed in multiple types of both parenchymal and nonparenchymal cells present in the chronically diseased liver: For instance, MIF is secreted by adipocytes and fibroblasts as well as several immune cells, endothelial cells and Kupffer cells upon inflammatory stimuli. Interestingly, as shown by our previous study, hepatocytes represent the main source of MIF within the liver during the progression of non-alcoholic steatohepatitis (NASH) (Heinrichs et al, 2021). In the liver, CD74 is expressed on hepatocytes as well as hepatic stellate cells (HSC) (Maubach et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…Immunohistochemical analysis revealed that the tumour cells themselves are the major source of enhanced MIF expression. The fact that hepatocytes, as the main cell type in liver, are primarily responsible for MIF production is supported by observations in alcohol-induced liver injury in humans (Marin et al, 2017) as well as in an experimental model of NASH in mice (Heinrichs et al, 2021). To test our hypothesis that hepatocyte-derived MIF exerts functional relevance during hepatocarcinogenesis, we performed the DEN/CCl 4 model in mice with a hepatocyte-specific Mif knockout.…”
Section: Macrophage Migration Inhibitory Factor Promotes Erk Phosphorylation In Hepatoma Cells In a Cd74-dependent Mannermentioning
confidence: 95%
“…This disease specific role of MIF in patients with AH is consistent with data from murine models, where MIF contributes to ethanol-induced liver injury (12)(13)(14), but may protect from high fat diet induced liver injury and chemically-induced liver fibrosis (39,40). Additional evidence for context specific roles of MIF was reported in a recent study, wherein the use of hepatocytespecific Mif knockouts revealed a previously unknown pro-fibrotic effect of MIF in diet-induced model of fibrosis in mice, contrasting with previous results utilizing global Mif knockouts (41).…”
Section: Discussionmentioning
confidence: 85%
“…A similar effect might also be seen during the course of NASH. While MIF conveys anti-steatotic effects on hepatocytes, it contributes to liver fibrogenesis in a murine model of NASH (MCD diet feeding) by skewing the intrahepatic immune milieu toward a pro-fibrotic polarization of innate lymphocytes ( 99 ).…”
Section: Immunological Mechanisms In Liver Fibrosismentioning
confidence: 99%